PENGEMBANGAN BUKU PENGAYAAN PENGETAHUAN "PANDANGAN FISIKA TERHADAP PERISTIWA MENCAIRNYA ES DI KUTUB" - Syifa Fauziah; Desnita Desnita; Cecep E Cecep E; Rustana Rustana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2067)
This research aim to develop knowledge enrichment book of ice melting in North Pole based on competence 3.9 grade XI, that is to analyze the indication of global warming, greenhouse effect, climate change, and the impact for life and environment. In this research, applied Research and Development Method refer to Dick & Carey. Survey has done to know the necessity of enrichment book in four schools, book stores, and Pusat Kurikulum dan Perbukuan. The result is availability of enrichment book with North Pole ice melting competence around 7 until 8 book titles. To evaluate the whole enrichment book, validation test is done to high schoolâ€™s students and giving the results as mean score percentage as 85% with details like 86% for content, 81% for presentation, 87% for language, and 85% for graphic. The results show that the content of enrichment book are able to increase studentâ€™s motivation to search deeper about North Poleâ€™s ice melting phenomenon, furthermore the presentation of sentences and illustrations that clarify the content. So it can be concluded that knowledge enrichment book â€œPhysics Opinion To North Pole Ice Melting Phenomenonâ€ obtain the Very Good predicate. Keywords: knowledge enrichment book, greenhouse effect, global warming, North Poleâ€™s Ice Melting